Syv Beowulf-anmeldere - Haarder, Andreas (Grundtvig-studier, 1968)
Seven Beowulf-Reviewers By Andreas Haar der.Beowulf has been received twice. First by an audience of Anglo-Saxons who must have commented on what they heard in various ways; secondly when Thorkelin’s edition appeared ( 181 5 ) to attract the attention of seven reviewers, none of them familiar with Old English, all of them obliged to approach the poem through a less than satisfactory version of it.The seven reviews analysed in the present article betray varying standards of critical ability. The contribution by Pem (Dansk Litteratur-Tidende 181 5 ) contains several sound critical comments. But although he touches upon the question of bipartition, and, like Grundtvig, compares the poem with Eddaic poetry, his concern is with the problem of origins, not with literary evaluation (I).Taylor (The Monthly Review 1816) is sympathetic towards the poem, but otherwise rather incompetent (II). Pia (Jenaische Literatur-Zeitung 18 16), who is a much more scholarly reviewer, criticizes Thorkelin on various points, and takes issue with him also on the question of genre. The poem can not be ranked as an epic. It lacks epic unity, Pia argues, because it deals with the whole life of the hero, and it lacks a proper epic theme. Monster-fights should be relegated to a different world (m ) .Outzen (Kieler Blätter 1816 ) points to the advanced cultural stage where the poem, perhaps written to educate a young prince, rightly belongs. The greatness claimed for the poem remains a postulate, however. The article is not a review proper, but a patriotic attempt to locate everything in Outzen’s “ Vaterland” (IV).Gumælius (Iduna 181 7 ), who is unable to improve sufficiently upon the poem as presented by Thorkelin, suggests that it was spoilt by a Christian redactor (V).Like Gumælius the reviewer in GgA (Göttingische gelehrte Anzeigen 1818 ) does not rate the aesthetic value of the poem highly. But he admits to his own complete dependence on Thorkelin’s Latin translation and shows some awareness of the limits imposed upon him as a critic (VI).Grundtvig (Nyeste Skilderie 181 5 ) discusses the many mistakes committed by Thorkelin and left unnoticed by Pem. The review shows him not only as a scholar who was in many cases right but also as a literary critic. The two functions are really interdependent, i. e. he is strongly aware that many of his suggestions make the poem better. A firm belief in the competence of the poet is a stimulus to his work. His evaluation of the poem as a whole is a striking evidence of his early conviction that it is a perfect work of art.Grundtvig’s ability to be an imaginative as well as a scholarly critic places him in a class by himself.